The Berenstain Bears and the slumber party - Berenstain, Stan, 1923-2005 (Berenstain, Stan, 1923-2005. First time books., 1990)
Lizzy Bruin's slumber party becomes even wilder when Too-Tall Grizzly and his friends decide to attend uninvited.